1976
DOI: 10.1172/jci108449
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil function in gram-negative rod bacteremia. The interaction between phagocytic cells, infecting organisms, and humoral factors.

Abstract: A B S T R A C T To assess the phagocytic and bactericidal function of neutrophils in the acute stages of gramnegative rod bacteremia, cells from 30 nonleukopenic patients were studied in a test system utilizing plasma obtained simultaneously with culture-positive blood, the autologous infecting strain, and two laboratory test strains of Staphylococcus aureus and Pseudomonas aeruginosa. Results were compared to those obtained with normal neutrophils and plasma. Patient and control plasma were simultaneously tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Specific 0 antisera did not increase phagocytosis, while K antibodies, did, according to Sjostedt (1946). Weinstein & Young (1976 found that Ki-containing strains from bacteraemia were relatively more resistant to opsonophagocytosis by normal human plasma and polymorphonuclear leucocytes than non-K 1 strains. Addition of K antibody increased the phagocytosis of K 1 bacteria, and the authors suggested that the low immunogenicity of the K1 antigen could explain the resistance to phagocytosis in normal plasma.…”
Section: Phagocytosismentioning
confidence: 93%
“…Specific 0 antisera did not increase phagocytosis, while K antibodies, did, according to Sjostedt (1946). Weinstein & Young (1976 found that Ki-containing strains from bacteraemia were relatively more resistant to opsonophagocytosis by normal human plasma and polymorphonuclear leucocytes than non-K 1 strains. Addition of K antibody increased the phagocytosis of K 1 bacteria, and the authors suggested that the low immunogenicity of the K1 antigen could explain the resistance to phagocytosis in normal plasma.…”
Section: Phagocytosismentioning
confidence: 93%
“…The role of complement has been clearly established experimentally (5,6) and indirectly confirmed in clinical situations by the demonstration ofdecreased opsonic activity in patients with C3 deficiency, and concomitant increased susceptibility to bacterial infections (7). Several clinical studies have also shown that serum complement levels and(or) opsonic activity could be depressed during acute septicemia (8)(9)(10). It could be therefore hypothesized that persistence of microorganisms in presence of PMN-s, as encountered in infected pleural effusions, might be a result of inadequate, complement-dependent opsonization of the infectious agent.…”
Section: Introductionmentioning
confidence: 97%
“…Bacterial counts at 30 hours varied considerably, but this did not affect the ability of the Scansystem to provide positive results. This is likely to be due to the fact that the Scansystem can detect both live and dead bacteria, so that the presence of bacterial species such as P. aeruginosa and S. epidermidis , which are frequently inhibited or killed in the presence of human plasma, 7,8 can still be detected provided some bacterial growth occurred. This is particularly important for contamination with P. aeruginosa because transfusion of small amounts of endotoxin produced by the growth of this organism can result in a fatal outcome.…”
Section: Discussionmentioning
confidence: 99%